Penyebab Instabilitas Ekonomi-Politik di Negara-negara Kepulauan Akibat Pandemi Covid-19: Studi Kasus Maladewa dan Kepulauan Bahama - Kurnia Zulhandayani Rizki; Namira Risqi Putri Muquita (Department of International Relations, University of Mataram, 2022)
ABSTRACT Covid-19 pandemic brings multi-sectoral impact which encourages economic weakening and carries political instability. In this case, developing countries are affected massively by the pandemic. Vulnerable economic stability and unsteady government management encourage the state to experience inability to adapt to the restriction imposed during pandemic. Some developing countries that are not depended on tourism as their economic spine, still have chance to recover through other sector than tourism. However, the phenomena during pandemic appear to be such a condition where developing countries, which are ‘tourism-dependent’, experience terrific economic contraction. Especially, the archipelagic state that rely on natural tourism as the main attraction. The archipelagic states that rely on tourism and experience economic contraction along with political instability are Maldives and Bahamas Islands. Keywords: Covid-19 pandemic; Maldives; Bahamas Islands; archipelagic state. ABSTRAK Pandemi Covid-19 memberikan dampak multi-sektoral yang mendorong melemahnya ekonomi hingga mengganggu stabilitas politik negara. Dalam hal ini, negara-negara berkembang merupakan objek yang terdampak pandemi cukup masif. Stabilitas ekonomi yang rentan dan manajemen pemerintahan yang goyah mendorong negara kesulitan beradaptasi dengan pembatasan yang diberlakukan selama pandemi. Beberapa negara berkembang yang tidak menggantungkan perekonomiannya pada pariwisata masih dapat memulihkan perekonomiannya dengan mengembangkan sektor lainnya sebagai penopang. Akan tetapi, melihat fenomena yang muncul di masa pandemi, maka dapat dilihat negara-negara berkembang yang bergantung pada sektor pariwisata mengalami kontraksi ekonomi yang cukup hebat. Terutama negara-negara kepulauan yang mengandalkan wisata alam sebagai destinasi andalannya. Negara-negara kepulauan yang bergantung pada pariwisata dan mengalami kontraksi ekonomi dan instabilitas politik antara lain yaitu Maladewa dan Kepulauan Bahama. Keywords: pandemi Covid-19; Maladewa; Kepulauan Bahama; negara kepulauan.